THE ANALYSIS OF ELVIRA EV-1 CHASSIS MECHANICAL PERFORMANCE WITH VARIOUS BEAM CROSS-SECTION - Wijianti, Eka Sari; Sarwono, Agus; Ariksa, Jeri; Saparin, Saparin; Adib, Adam Zuyyinal (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Elvira EV-1, as an electric vehicle (EVs) has become one of the latest developments that contributes to achieving sustainable and reliable transportation. These EVs were built to serve as a relevant solution for campus operational mobility. However, at the core of its framework system, Elvira EV-1 still uses a ladder-type chassis, which is inferior to other types of chassis in terms of torsional rigidity. Therefore, to enhance its mechanical performance, this study determined the best option of beam cross-section for the Elvira EV-1 chassis. There were three types of the selected beam section, namely rectangular, I-beam, and C-channel. The mechanical performance of each type of chassis was examined using the Frame Analysis module provided by Autodesk Inventor. The results show that the rectangular chassis experienced the highest bending stress of the other types of chassis due to its low moment of inertia, which is almost 26.27% higher. Nonetheless, with the same setup, the shear stress that occurred at the C-channel type of chassis was greater than its material. The chassis would fail under the load subjected to it. Similarly, I-beam chassis has the maximum torsional stress greater than the yield strength of the material due to low torsional rigidity. In addition, the mass of the chassis with rectangular section provided a more lightweight structure, about 36,92% lower than the other type of chassis. According to these findings, it can be concluded that the chassis with a rectangular section has promising performance to be an option as the Elvira EV-1 chassis.